Circulating irisin levels of prenatal and postnatal patients with gestational diabetes mellitus: A systematic review and meta-analysis. (February 2020) - Cui, Lingling; Qiao, Tianyi; Xu, Fan; Li, Zhonglei; Chen, Tingting; Su, Hongli; Chen, Guixia; Zhang, Li; Xu, Dongmei; Zhang, Xiaofeng
Highlights: The blood irisin levels for GDM group were significantly lower than that for control group during pregnancy. There was no significant difference of irisin levels in the postpartum blood and cord blood between the two groups. Irisin may play an important role in the occurrence and development of GDM. Abstract: Aims: At present, there are few studies on the relationship between circulating irisin levels and gestational diabetes mellitus (GDM), and the results are inconsistent. Therefore, this study conducts a systematic review and meta-analysis to comprehensively discuss the role of irisin in the occurrence and development of GDM. Methods: We searched the articles on the relationship between GDM and circulating irisin levels up to September 2019, using the CNKI, WANFANG-DATA, PubMed and the Web of Science databases. Results: Twenty two articles including 3563 participants were selected in the meta-analysis. Meta-analysis found the blood irisin levels for GDM group were significantly lower than that for control group during pregnancy(SMD = −0.88, 95%CI: −1.34, −0.42, P < 0.001). However, there was no significant difference of irisin levels in the postpartum blood and cord blood between the two groups (SMD = −1.44, 95 % CI : −3.79, 0.92, P = 0.23; SMD = −0.17, 95 % CI : −0.59, 0.25, P = 0.42, respectively). Conclusions: Compared with the control group, irisin levels in the GDM group during pregnancy are lower. However, it is no significant difference of irisin levels in the postpartum blood and cord blood. Irisin may play an important role in the occurrence and development of GDM, which needs further research to demonstrate.